2013
DOI: 10.1002/ijc.27984
|View full text |Cite
|
Sign up to set email alerts
|

The dual role of the novel Wnt receptor tyrosine kinase, ROR2, in human carcinogenesis

Abstract: The Wnt signaling pathway is involved in the development and progression of many human cancers, yet attempts to target the pathway therapeutically have been disappointing to date. The recent discovery that the ROR2 receptor tyrosine kinase (RTK) is a novel Wnt receptor provides the potential to target the non-canonical Wnt pathway for cancer treatments. As a member of the RTK superfamily of surface receptors ROR2 appears to possess dual roles as a tumor suppressor or activator depending on tumor type. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 62 publications
4
71
0
Order By: Relevance
“…Acquisition of ROR1 by such cells may be an important step in leukemogenesis, allowing the neoplastic complex with LRP5/6 in response to canonical Wnt factors, such as Wnt3a. Through such a mechanism, Wnt5a inhibits the capacity of Wnt factors, such as Wnt3a, to induce canonical Wnt signaling (27,33,(49)(50)(51). Furthermore, studies have demonstrated that isolated overexpression of ROR2 in 293 cells actually enhanced the capacity of Wnt5a to repress expression of β-catenin target genes (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquisition of ROR1 by such cells may be an important step in leukemogenesis, allowing the neoplastic complex with LRP5/6 in response to canonical Wnt factors, such as Wnt3a. Through such a mechanism, Wnt5a inhibits the capacity of Wnt factors, such as Wnt3a, to induce canonical Wnt signaling (27,33,(49)(50)(51). Furthermore, studies have demonstrated that isolated overexpression of ROR2 in 293 cells actually enhanced the capacity of Wnt5a to repress expression of β-catenin target genes (28).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ROR2 also can repress transcription of Wnt target genes and modulate Wnt signaling by sequestering canonical Wnt ligands, thereby serving as a tumor suppressor in different cell contexts (27,28). Although studies have shown that ROR1 or ROR2 can associate with other proteins to modify canonical Wnt signaling or induce noncanonical signaling (29,30), ROR1 and ROR2 are each considered to function independently of one another.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Wnt5a ligand mediates intracellular signaling via a ␤-catenin-independent (noncanonical) Wnt pathway to regulate cell polarity and migration in a variety of tumor types, including metastatic melanoma (40), thyroid carcinoma (41), and colon cancer (42). Wnt5a associates with tyrosine kinase-like orphan receptor 2 (ROR2) (43,44), which leads to Rho GTPase (RhoA and Rac)-dependent activation of the Wnt-Jun N-terminal kinase (JNK) pathway and activation of the WntCa2 ϩ pathway through calcium/calmodulin-dependent protein kinase II (CaMKII) (45)(46)(47). The role of this noncanonical Wnt pathway in trophoblast migration has not been investigated so far and needs to be elucidated given the importance of Wnt signaling in embryonic development and disease.…”
mentioning
confidence: 99%
“…instance, the protein expression of ROR2 was reported to be significantly decreased in hepatocellular carcinoma (HCC) tissues compared with adjacent non-tumorous tissues, and loss of ROR2 expression was associated with poor prognosis, suggesting that ROR2 may act as a tumor suppressor in HCC (26). By contrast, ROR2 was suggested to play an oncogenic role in certain other cancers, including melanoma, renal cell cancer and oral squamous cell carcinoma (27)(28)(29).…”
mentioning
confidence: 99%